Annealing of Aluminium Implanted 4H-SiC: Comparison of Furnace and Lamp Annealing - Rambach, Martin; Bauer, Anton; Frey, Lothar; Friedrichs, Peter; Ryssel, Heiner (Materials Science Forum, 2005)
Furnace annealing and lamp annealing of aluminum implanted layers in 4H silicon carbide (SiC) were investigated with respect to surface degradation and electrical parameters. A sheet resistance of about 20kΩ/□ was obtained for an aluminum implantation dose of 1.2·1015cm-2 and annealing in the furnace at 1700°C for 30min. For the same implantation dose, lamp annealing at 1770°C for 5min resulted in a three times higher sheet resistance of 60kΩ/□. The surface roughness was best for the lamp system and stayed below 1nm for Al doses lower than 1·10 15 cm-2.
UnivIS-Import:2017-07-10:Pub.2005.tech.IE.LEB.anneal
Keywords: Annealing; Ion implantation; Sheet resistance; Surface roughness